New Sustainable Secure Nuclear Industry Based on Thorium Molten-Salt Nuclear Energy Synergetics (THORIMS-NES) - Furukawa, Kazuo; Greaves, Eduardo D.; Erbay, L. Berrin; Hron, Miloslav; Kato, Yoshio (IntechOpen, 2011)
None